Principal component analysis of monthly mean Area surface temperature over the Arabian Sea, Bay of Bengal and north Indian Ocean for two Contrasting sets of monsoon years - BALAKRISHNAN , T. K.; JASWAL, A. K.; SINGH , S.S..; SRIVASTAVA, H. N. (MAUSAM, 1993)
The spatial distribution and temporal variation of the monthly mean SSTA over the Arabian Sea, Bay of Bengal and the north Indian Ocean were investigated for a set of contrasting years of monsoon over the period 1961-80 for months April through July using Empirical Orthogonal Function (EOF) technique with a view to identify regions that are significantly related to the monsoon rainfall. Over 75% of the total variance is, explained by the first mode EOF. SSTA over the north and northeast Arabian Sea during pre-monsoon months were found to be possible indicators of the ensuing monsoon activity. The higher eigen vectors in May over northeast Arabian Sea may signal good monsoon and vice versa. In June there is a marked contrast in the distribution of SST over the Arabian Sea between the two sets of the years the eastern Arabian Sea IS warmer for the deficient monsoon years while the entire Arabian Sea except over the extreme north Arabian Sea is cool during good monsoon years. There is formation of SSTA over the equatorial Indian Ocean area close to Indonesian island commencing from May which is more marked in June and is positively correlated with seasonal rainfall activity over India.